Implementasi Pendidikan Islam Integratif: Studi Ekploratif Di SMA Nurul Ulum, Demak - Aldi Mustofa; Moh. Sholihuddin (Getpress Management Journals, 2025)
This study aims to elaborate an integrative conceptual model of Islamic Education as implemented at SMA Nurul Ulum Demak. The research employed a qualitative approach, with data collected through observations, in-depth interviews with subject teachers, and analysis of school documents. Thematic analysis was conducted to identify key themes within the school’s integrative Islamic education practices. The findings indicate that the integrative model of Islamic education strengthens students’ emotional regulation, motivation, social interaction, and moral behavior. Teachers serve as exemplars, mentors, and learning facilitators who harmonize Islamic educational values with psychological principles to support students’ holistic intelligence and character. The integration of Islamic pedagogical traditions such as ta‘lim, tarbiyah, ukhuwah, ihsan, and tazkiyah forms a comprehensive framework for student development. The main challenges in implementing this model include teachers’ limited understanding of students’ psychological development and the strong influence of the surrounding social environment. Therefore, further integration is required through enhanced teacher training and greater involvement of families and communities to ensure the success of Islamic education in the modern era.